The hospital ethical climate and its meaning in nursing work. A review of research results - Dziurka, Magdalena; Ozdoba, Patrycja; Jedynak, Anna; Dobrowolska, Beata (Medical Studies/Studia Medyczne, 2021)
The ethical climate reflects the principles and guidelines of an organisation. A positive ethical climate is characterised by a common vision of caring for work, in which the therapeutic team members inform and support each other, and which meets the needs of patients and their families. The aim of this study was to analyse nursing research on the hospital’s ethical climate conducted with the Hospital Ethical Climate Survey (HECS) and to analyse factors which correlate and are related to nurses’ work. A critical review of the literature from 1995 to 2021 was conducted with the following keywords: ethical climate, hospital ethical climate survey, HECS, and nurses. The hospital ethical climate correlates with nurses’ moral sensitivity/courage/distress, job satisfaction, job burnout, and ethical leadership. This makes it possible to monitor and assess elements of the organisation climate and how they influence nurses’ professional performance. This in turn helps nursing managers to develop strategies to promote better working conditions for nurses, improve job satisfaction, and prevent intent to change their workplace.